2019
DOI: 10.1093/milmed/usy296
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the Military: Understanding Rates and Risk Factors Across the United States’ Armed Forces

Abstract: This paper presents data from the United States Department of Defense Suicide Event Report System for years 2012–2015 to detail descriptive, longitudinal rate data and risk factor profiles associated with military suicide. The annual findings were aggregated from all U.S. military suicide deaths and suicide attempts. Data elements included the most common method of suicide (firearms), most common behavioral health diagnoses (substance abuse/dependence), common life stressors (failed intimate–partner relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 9 publications
1
37
0
2
Order By: Relevance
“…These rates have increased nearly every year for more than a decade (American Foundation for Suicide Prevention, 2021) despite the implementation of suicide prevention initiatives (Bagley et al., 2010; Bryan et al., 2012). Suicide rates also have risen among subpopulations that historically have had very low suicide rates, such as United States military personnel (Kuehn, 2009; Pruitt et al., 2019).…”
Section: Aims Of the Present Reviewmentioning
confidence: 99%
“…These rates have increased nearly every year for more than a decade (American Foundation for Suicide Prevention, 2021) despite the implementation of suicide prevention initiatives (Bagley et al., 2010; Bryan et al., 2012). Suicide rates also have risen among subpopulations that historically have had very low suicide rates, such as United States military personnel (Kuehn, 2009; Pruitt et al., 2019).…”
Section: Aims Of the Present Reviewmentioning
confidence: 99%
“…A study by Pruitt et al [25] showed that while during the years 2012-2015 the rate of death by suicide for male soldiers was between 20.5 and 24.8 per 100,000 US service members, the rate for female soldiers was 11.7 per 100,000 US service members, namely about half of the men's rate. Firearms were found to be the most common method of suicide (62.3%), followed by hanging or asphyxiation (29.8%) [25].…”
Section: The Gender Paradox In Suicide and Various Armed Forces 21 United States Armed Forcesmentioning
confidence: 99%
“…A study by Pruitt et al [25] showed that while during the years 2012-2015 the rate of death by suicide for male soldiers was between 20.5 and 24.8 per 100,000 US service members, the rate for female soldiers was 11.7 per 100,000 US service members, namely about half of the men's rate. Firearms were found to be the most common method of suicide (62.3%), followed by hanging or asphyxiation (29.8%) [25]. Results from the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS) conducted in the US military, showed that female service members attempt suicide more often than males [10,13,24,26].…”
Section: The Gender Paradox In Suicide and Various Armed Forces 21 United States Armed Forcesmentioning
confidence: 99%
“…Fato esse provavelmente relacionado ao impacto do estresse na questão de saúde pública, pois influencia tanto na questão dos gastos com tratamento de depressão, ansiedade, burnout, quanto no aspecto psicossocial de casos de suicídio (LOGAN et al, 2016;PRUITT et al, 2019;QUEIRÓS et al, 2020).…”
Section: Lista De Figurasunclassified